Improving Teacher Performance in Creating Innovations for Student Learning - Isma. Hayati Daulay; Sulasmi Sulasmi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This article aims to describe how teacher performance can be improved by creating student innovation in learning. This paper uses qualitative research methods and literature review. The collected data comes in the form of secondary and primary data, which are analyzed and presented by the authors in a descriptive manner. The results of the analysis indicate that in order to improve teacher performance and develop students' innovative learning abilities, educators must have the following: 1. Teachers must be able to use different learning strategies to communicate learning content. 2. Teachers must be able to use learning methods and media in learning activities. 3. Teachers must be able to engage students in any learning situation. 4. Teachers must be able to prepare learning in a playful way that brings different innovations to students in each lesson. 5. Teachers need to master technology Great reference for students in today's digital age. Keywords: performance, innovation